Physical Disability in the Workplace: A Comprehensive Review and Unifying Framework - Lee, Wyatt E.; Roccapriore, Ashley Y.; Lohrke, Franz T.; Reutzel, Christopher R. (Journal of Management, 2026)
In the United States, more than a quarter of the working-age population experiences physical disabilities that shape workplace participation and career outcomes. Drawing on 168 articles, we synthesize the management literature to develop a unifying framework of focal mechanisms, workplace outcomes, and boundary conditions. In doing so, we offer a clear definition of physical disability, long absent from management research. We also highlight the fragmented theoretical and methodological landscape, in which most studies aggregate disability types, overlooking critical heterogeneity. Our review charts a path forward by identifying key gaps, outlining directions for future scholarship, and emphasizing the need for stronger theoretical grounding and methodological rigor. Finally, we discuss implications for policy and practice, underscoring how greater inclusion of persons with physical disabilities can advance various workplace outcomes.